2018
DOI: 10.1017/s095026881800170x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the prevalence of chronic hepatitis C virus infection in New York City, 2015

Abstract: Chronic hepatitis C virus (HCV) infection is the most common blood-borne infection in the USA. Estimating prevalence is critical for monitoring diagnosis, treatment, and cure and for allocating resources. Surveillance data reported to the New York City (NYC) Health Department, 2000-2015, were used to estimate HCV prevalence in NYC in 2015. The numbers who died, out-migrated or whose last RNA test was negative were removed from the count of people reported with HCV. A simulation model was used to remove estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The above assumptions that were required to project NHANES results to the state level resulted in prevalence estimates that differed dramatically from the evidence available from state‐level HCV surveillance data. For example, a recent surveillance‐based prevalence estimate published for New York City found that there were approximately 116 000 persons living with chronic, RNA‐positive infection in 2015, after accounting for mortality, outmigration, the proportion of persons undiagnosed and the number of persons cured with new direct‐acting antivirals . This estimate is identical to what Rosenberg et al found for the entirety of New York State's 19.8 million residents, including New York City's 8.6 million residents.…”
supporting
confidence: 59%
“…The above assumptions that were required to project NHANES results to the state level resulted in prevalence estimates that differed dramatically from the evidence available from state‐level HCV surveillance data. For example, a recent surveillance‐based prevalence estimate published for New York City found that there were approximately 116 000 persons living with chronic, RNA‐positive infection in 2015, after accounting for mortality, outmigration, the proportion of persons undiagnosed and the number of persons cured with new direct‐acting antivirals . This estimate is identical to what Rosenberg et al found for the entirety of New York State's 19.8 million residents, including New York City's 8.6 million residents.…”
supporting
confidence: 59%
“…We published a detailed analysis of our treatment outcomes [35] . While DOHMH surveillance data are presumed to capture all people tested for HCV in NYC, and the data have been used for other epidemiological studies of HCV in NYC [36] , there could be reporting or deduplication errors that could not be ascertained. Finally, we cannot generalize our results to other US jail systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we cannot definitively identify most incident HCV cases using DOHMH surveillance data. Because most HCV-infected individuals are asymptomatic and go undiagnosed for many years after initial infection, a new HCV diagnosis does not represent a new HCV infection in many cases 1 4. The exclusion of HIV/HCV coinfected MSM who were diagnosed with HCV before HIV or within 90 days of HIV was intended to exclude known cases of prior HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a major source of morbidity and mortality worldwide, as chronic HCV infection can result in liver failure, cirrhosis and hepatocellular carcinoma 1 2. As of 2016, as many as 2.4 million US residents were living with chronic HCV infection, including an estimated 116 000 in New York City (NYC) 3 4. HIV coinfection among persons with HCV carries an elevated risk of HCV disease progression, liver disease, cirrhosis and death 1 2 5.…”
Section: Introductionmentioning
confidence: 99%